Efisiensi Bank Pembangunan Daerah Menggunakan Data Envelopment Analysis dan Stochastik Frontier Analysis - Sengkey, Marthen (JBE (Journal of Business and Economics); Volume 8 No.1, 2009 JBE UNKLAB, 2009)
The study employs the three-stage banking models to investigate the performance of 26 state banks in Indonesia from 1994 to 2004.  Data envelopment analysis (DEA) results indicate that the average efficiency of state banks was 38.3 percent and deteriorated when the financial crisis struck Indonesia in 1997.  Using stochastic frontier analysis (SFA) method, findings suggest that, on average, banks obtained 62.8 percent efficiency.  Findings also suggest that banks’ technical inefficiency is affected significantly by government intervention, location, and ownership.  Finally, state banking performance was tested by correlating the DEA and SFA models and found no statistically significant correlation.  Reported new findings of this paper are additions to banking efficiency literature.